Computer model for evaluating performance and economic risk at the level of farms of different sizes - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Computer Model for performance evaluation and economic risk is a model complex based on appropriate methodologies with specific indicators, necessary to administer the agricultural farm, management, efficient and increase its productivity. System of indicators is intended as a centralized source of information necessary to improve economic performance and efficient use of production factors by which to ensure the development of commercial farms, efficient use of input, raising yields and improve economic performance.
Keywords: 330; computer model; agricultural management; economic and financial indicators; economic risk